1996
DOI: 10.1016/s0266-7681(96)80039-8
|View full text |Cite
|
Sign up to set email alerts
|

Total Wrist Fusion

Abstract: Twenty cases of total wrist fusion, performed for post-traumatic conditions, were reviewed objectively, subjectively and radiologically. All patients were satisfied with the position of the fused wrist and had good pain relief. All patients would have had the procedure sooner, having had an average of three operations on the wrist before the fusion. There was a high complication rate (45%), although only four patients required further procedures for those complications. Hand function, as assessed by the Jebsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 7 publications
0
21
0
4
Order By: Relevance
“…Salvage procedures like PRC and 4CF are two of the more popular operations but both have drawbacks, including loss of grip strength and movement respectively. Another procedure, namely wrist arthrodesis, while surprisingly still considered the ultimate solution for post-traumatic wrist osteoarthritis, 10 unsurprisingly still results in poor hand function 11 . While many patients scheduled for these procedures are demanding in respect to the function they need in the wrist to enable them to return to work and leisure activities, this paper challenges the assumption that there are no surgical alternatives, and questions the promotion and use of the Amandys®.…”
Section: Discussionmentioning
confidence: 93%
“…Salvage procedures like PRC and 4CF are two of the more popular operations but both have drawbacks, including loss of grip strength and movement respectively. Another procedure, namely wrist arthrodesis, while surprisingly still considered the ultimate solution for post-traumatic wrist osteoarthritis, 10 unsurprisingly still results in poor hand function 11 . While many patients scheduled for these procedures are demanding in respect to the function they need in the wrist to enable them to return to work and leisure activities, this paper challenges the assumption that there are no surgical alternatives, and questions the promotion and use of the Amandys®.…”
Section: Discussionmentioning
confidence: 93%
“…17 A separate study by Field et al, on 20 patients following total wrist fusion found a 25% incidence of "ulnar carpal pain" not otherwise specified. 19 Ascertaining the incidence of this complication based on existing literature is not possible, but it is clearly a rare complication based on existing reports. It is possible, however, that the incidence is higher than current literature suggests, as "ulnar carpal pain" could be due to PT arthritis, although numerous other etiologies of this pain are possible as well.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme extension of the wrist in a fused position might cause median nerve-related problems, and is cosmetically less acceptable. Field et al 17 concluded that the most suitable position for the wrist remains uncertain. The AO plate incorporates 10° of extension and neutral deviation.…”
Section: Discussionmentioning
confidence: 99%
“…A total wrist fusion is considered a salvage operation, with the prerequisite that it improve persistent wrist pain. 17 Because of the limitations after a wrist fusion, the procedure is often postponed, while several other motionpreserving operations are offered. Meads 4 states that a wrist fusion should be recommended earlier, limiting the number of operations before the wrist fusion, but the patient should be warned about the limitations after the fusion.…”
Section: Discussionmentioning
confidence: 99%